Statutory Auditors' Independence in Protecting Stakeholders' Interest An Empirical Study - Roy, Mitrendu Narayan (Springer International Publishing, 2018)
Corporate failures and accounting scandals have shaken the foundations of investors' confidence in the transparency, integrity and accountability of corporations and financial markets. There have also been public disquiet about the role of professional auditors and audit firms, who had been associated with these corporate scandals. Written from a global perspective, the book assists in understanding the gravity of independent attitude of statutory auditors in protecting stakeholders' interest and examines the effectiveness of the existing standards and other legal and regulatory requirements in enforcing statutory auditors' independent engagement. It then suggests modifications in those regulations. The study has been made through seven chapters in order to address empirically statutory auditors' independence in protecting stakeholders' interest. Primary audiences of the book are researchers in finance and control, students, and professionals in the field of accounting and auditing. Dr. Mitrendu Narayan Roy is an Assistant Professor, Goenka College of Commerce and Business Administration for more than 2 years. He did his M.Com. from the University of Calcutta in 2010 and qualified NET with JRF under UGC in 2011. He obtained his Ph.D. from the University of Calcutta under the supervision of Dr. Siddhartha Sankar Saha in 2016. He has published more than 25 research papers in refereed journals along with a joint authorship for research oriented book published by Emerald Publishing Ltd., UK. Dr. Siddhartha Sankar Saha is a Professor of Commerce in the Department of Commerce at University of Calcutta, Kolkata, West Bengal, India. He served department of commerce (Accounting and Finance), St. Xavier's College (Autonomous), Kolkata, India previously. He obtained his PhD in Finance from the Department of Commerce, University of Calcutta. He has two decades of teaching experience at undergraduate and postgraduate levels in accounting, finance and control in universities and business schools, and is presently supervising a number of MPhil and PhD scholars. He has completed a Major Research Project (MRP) funded by the UGC, New Delhi, India and is currently conducting another MRP funded by the ICSSR, New Delhi, India. Dr. Saha has 122 research papers to his credit in journals of national and international repute, conference proceedings of national and international conferences and edited volumes. Dr. Saha has also been invited to chair sessions and deliver keynote speeches at international conferences in India and abroad. He has become a prolific author and has contributed ten books in the field of finance published by publication houses of national and international repute, such as McGraw-Hill Education, Taxmann, LAP Lambert Academic Publishing, Scholars' Press and Emerald Publishing.